2018
DOI: 10.1016/j.ram.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assessment of honey in México

Abstract: Honey is a product used as a natural sweetener and in several regions of Mexico and other countries it is also used as a therapeutic agent. Microbiological contamination of honey can occur during its extraction and handling. Due to the use and consumption of honey we highlighted here the importance of the assessment of its microbiological quality. One thousand nine hundred twenty samples obtained from 8 honey-producing states from Mexico were analyzed. From these samples, 40.5% (777/1920) did not comply with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
4
23
0
3
Order By: Relevance
“…The data obtained from physicochemical study indicated that honey samples originating from the two different climatic zones (transitional between the continental moderate and oceanic moderate one vs. monsoon tropical) differ in case of pH, water activity and water content. In the present study, the pH value of the honeys of Polish and Thai samples (Table 2) were 3.3-4.9, which is consistent with other authors findings [15,16,33]. None of the normative acts imposes a minimum or maximum pH or water activity values.…”
Section: Discussionsupporting
confidence: 92%
“…The data obtained from physicochemical study indicated that honey samples originating from the two different climatic zones (transitional between the continental moderate and oceanic moderate one vs. monsoon tropical) differ in case of pH, water activity and water content. In the present study, the pH value of the honeys of Polish and Thai samples (Table 2) were 3.3-4.9, which is consistent with other authors findings [15,16,33]. None of the normative acts imposes a minimum or maximum pH or water activity values.…”
Section: Discussionsupporting
confidence: 92%
“…However, one specie, namely Peanibacillus larvae is the causative agent of diseases lethal to honeybees—American foulbrood. In fact, bee brood is the only established host for P. larvae [ 37 , 38 ]. On the basis of the analysis of the sequence of 16S rRNA, we were not able to determine if the producing strain is P. larvae or belongs to another species of the genus Paenibacillus .…”
Section: Discussionmentioning
confidence: 99%
“…Only one sample from present study has demonstrated the growth inhibition of P. aeruginosa ATCC 27857 and was described by BLAST as Staphylococcus sp., which suggests that this strain is more likely to be an environmental contamination than a natural microflora residing in honey. According to Vázquez-Quiñones et al [ 38 ], inadequate handling (packaging, storage, insects, or even insufficient decontamination) of honey is the main reason for S. aureus contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Además, al tratarse de levaduras osmotolerantes, generalmente inocuas y con capacidad de mantenerse viables en las condiciones antimicrobianas de la miel (Snowdon & Cliver, 1996;Aurongzeb & Azim, 2011;Vázquez-Quiñones et al, 2018) y del néctar de las plantas, en presencia de fitoquímicos y alta presión osmótica (Herrera et al, 2009;Herrera et al, 2010), serían buenas candidatas para ser utilizadas en el control de mohos patógenos, en ensayos a campo, o durante el almacenamiento de granos y semillas. La levadura N°3 L. thermotolerans, resultó efectiva para el control in vitro de todos los mohos testeados.…”
Section: Discussionunclassified
“…Las propiedades antimicrobianas, se le han atribuido principalmente al peróxido de hidrógeno y a varios compuestos fitoquímicos, como flavonoides, fenoles y ácidos orgánicos; por este motivo tiene un número reducido de microorganismos, y sólo se encuentran viables, aquellos que están adaptados a estas condiciones (Snowdon & Cliver, 1996;Bakier, 2009;Gomes et al, 2011;Velásquez Giraldo et al, 2013). Además, la alta osmolaridad y baja actividad agua no permiten el desarrollo de microorganismos que provienen de fuentes de difícil control, como el polvo, el aire, el suelo y el néctar (Snowdon & Cliver, 1996;Spencer & Spencer, 1997;Vázquez-Quiñones et al, 2018). Los microorganismos presentes en la miel pueden influenciar su estabilidad y calidad higiénica (Vica et al, 2009).…”
Section: Introductionunclassified